2003
DOI: 10.1124/mol.63.6.1273
|View full text |Cite
|
Sign up to set email alerts
|

Diazonamide A and a Synthetic Structural Analog: Disruptive Effects on Mitosis and Cellular Microtubules and Analysis of Their Interactions with Tubulin

Abstract: The marine ascidian Diazona angulata was the source organism for the complex cytotoxic peptide diazonamide A. The molecular structure of this peptide was recently revised after

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
1
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(68 citation statements)
references
References 32 publications
2
63
1
2
Order By: Relevance
“…Diazonamide A is an inhibitor of microtubule assembly, arresting the process of cell division in cultures exposed to treatment. Examination of treated cells reveals a loss of spindle microtubule assemblies and also microtubules associated with the interphase stage of the cell cycle (Cruz-Monserrate et al 2003). One tunicate living in the crystal waters of West Indies coral reefs and mangrove swamps, Ecteinascidia turbinata, turned out to be the source of an interesting anticancer drug called Ecteinascidin 743 (ET-743; Etrabectedin, 5) first isolated in 1990 (Rinehart et al 1990;Wright et al 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Diazonamide A is an inhibitor of microtubule assembly, arresting the process of cell division in cultures exposed to treatment. Examination of treated cells reveals a loss of spindle microtubule assemblies and also microtubules associated with the interphase stage of the cell cycle (Cruz-Monserrate et al 2003). One tunicate living in the crystal waters of West Indies coral reefs and mangrove swamps, Ecteinascidia turbinata, turned out to be the source of an interesting anticancer drug called Ecteinascidin 743 (ET-743; Etrabectedin, 5) first isolated in 1990 (Rinehart et al 1990;Wright et al 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Some other peptides from marine sources, such as Diazonamide A [65,66], Scleritodermin A [67,68], Hemiasterlin [6972], Desmethoxymajusculamide C (DMMC) [73] and Milnamide D [74] have been observed to display potent inhibition of tubulin polymerization in different cancer cells. Diazonamide A, a complex cytotoxic peptide, was isolated from the marine ascidian Diazona angulata [65].…”
Section: Peptides That Affect the Tubulin-microtubule Equilibriummentioning
confidence: 99%
“…Diazonamide A, a complex cytotoxic peptide, was isolated from the marine ascidian Diazona angulata [65]. Diazonamide A and the analog have a unique binding site on tubulin differing from the Vinca alkaloid and Dolastatin 10 binding sites.…”
Section: Peptides That Affect the Tubulin-microtubule Equilibriummentioning
confidence: 99%
“…However, the binding of dolastatin 15 was inhibited not only by cryptophycin 1 and dolastatin 10, but also by halichondrin B and vinca alkaloids. The vinca domain seems to be located in β-tubulin at the inter-dimer interface between α-tubulin and β-tubulin subunits in each protofiber (Gigant et al 2005), suggesting that these toxins do not bind to the vinca domain itself, but the binding site(s) for these toxins consist(s) of a series of overlapping domains on the surface of tubulin (Cruz-Monserrate et al 2003). This is consistent with the finding that hemiasterlin binds to helix H10 on α-tubulin which interacts across the interdimer interface with helix H6 of β-tubulin (Nunes et al 2005).…”
Section: Fig 11mentioning
confidence: 99%
“…It is an unusual alkaloid isolated from the colonial ascidian Diazona chinensis (Lindquist et al 1991) and its chemical structure was later revised by chemical synthesis (for review, see Ritter and Carreira 2002). COMPARE analysis predicted that it would be a tubulin toxin; subsequently it was shown to inhibit tubulin polymerization (IC 50 = 0.3-0.9 μM) and GTP binding (Cruz-Monserrate et al 2003). However, further study revealed that its inhibitory effect on cell division is mediated by ornithine δ-amino transferase rather than tubulin (Wang et al 2007).…”
Section: Othersmentioning
confidence: 99%